Human Resources Management Strategy to Create a Sustainable Competitive Advantage - Lenny Christina; Indra Siswanti; Yusliza Mohd Yusoff; Zikri Muhammad (Jurnal Abdimas Perbanas, 2023)
Competition for MSME players is getting tougher supported by increasingly developing technological advances, demanding MSME players to be able to adapt quickly to these changes. In order to survive in this competition, MSMEs are required to always be ready to face dynamic market changes.Today's company competitiveness no longer lies in the superiority of product and process technology or having a large market share and large capital, but how a company has quality human resources by increasing competitive advantage in a sustainable manner. With increasingly complex challenges, the role of HRM to be able to achieve competitive advantage is to be a pioneer in facing an ever-changing environment. These environmental changes require companies to always improve their performance or productivity. This can be achieved with a human resource management strategy that can respond to environmental changes